An In Situ One‐Pot Synthetic Approach towards Multivariate Zirconium MOFs. (21st April 2016) - Sun, Yujia; Sun, Lixian; Feng, Dawei; Zhou, Hong‐Cai
Abstract: Chemically highly stable MOFs incorporating multiple functionalities are of great interest for applications under harsh environments. Herein, we presented a facile one‐pot synthetic strategy to incorporate multiple functionalities into stable Zr‐MOFs from mixed ligands of different geometry and connectivity. Via our strategy, tetratopic tetrakis(4‐carboxyphenyl)porphyrin (TCPP) ligands were successfully integrated into UiO‐66 while maintaining the crystal structure, morphology, and ultrahigh chemical stability of UiO‐66. The amount of incorporated TCPP is controllable. Through various combinations of BDC derivatives and TCPP, 49 MOFs with multiple functionalities were obtained. Among them, MOFs modified with FeTCPPCl were demonstrated to be catalytically active for the oxidation of ABTS. We anticipate our strategy to provide a facile route to introduce multiple functionalities into stable Zr‐MOFs for a wide variety of potential applications.